Development and validation of educational-assistance technology for self-care for pregnant trans men during prenatal care - Matheus Emanuel de Castro Henrique; Francisco de Sales Clementino; Matheus Madson Lima Avelino; Eliane Santos Cavalcante; Ellany Gurgel Cosme do Nascimento; João Mário Pessoa Júnior (Revista Brasileira de Saúde Materno Infantil)
Abstract Objectives: to describe the process of developing and validating the content of an educational-assistance technology for self-care for pregnant trans men during prenatal care. Methods: this is a methodological study with a quantitative approach that encompassed two main stages, namely: i) development of the “Pregnancy Handbook” technology; and, ii) validation of content and appearance by a committee of expert judges. In the validation stage, the Delphi technique was applied to a group of seven judges, who responded to a questionnaire using the Likert scale. To evaluate the suitability of the instrument, the Content Validity Index (CVI) and the Content Validity Coefficient (CVC) were used. Results: the educational-assistance technology evaluated achieved a satisfactory CVC (0.90) and a CVI with excellent agreement (0.94), and showed excellent agreement between the expert judges regarding its content and appearance. Conclusion: the validated educational-assistance technology brings potential in prenatal care for trans pregnant women in the context of comprehensive health care.